Seropositivity and Risk Factors of HBV and HCV in Transgender Population in an Urban Area of Bangladesh - Mahmood, Abdullah Al; Shams, Tarek; Shahed Chowdhury, Mohammed Salahuddin; Gani, A B M Shakil; Chowdhury, Dilip; Raha, Aloke Kumar; Ghose, Aniruddha (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: The burden of HBV and HCV infections in the transgender population remains an underestimated issue. Determining the prevalence of these infections in transgender people could be important for health policymakers and health workers to develop a screening programs and hepatitis B vaccination program for this high-risk group. The study aimed to determine the prevalence of HBV and HCV infection and the risk factors for HBV and HCV infections among the transgender populations of Chattogram, Bangladesh. Materials and methods: This was a cross sectional study was conducted from January to June 2022. A conveniently selected 231 transgender individuals from health awareness campaign programs, private chambers and different health facilities of Chattogrm, Bangladesh, were included. Self-reported risk factors data were collected, and blood samples were obtained from the subjects and sent for Hepatitis B surface Antigen (HBsAg) and antibody to HCV (anti-HCV) tests. Results: The prevalence of HBsAg (+) and anti-HCV (+) was respectively 4.8% (11/231) and 0.4% (1/231), and 12.6% had a positive family history of HBV. Seventy-one (30.6%) had received dental treatment, 21 (9.1%) received blood transfusion, 75 (32.5%) were sharing nail cutter, 13 (5.2%) were shaving in the saloon, 5 (2.2%) had history of substance abuse, 221 (95.7%) pierced nose/ear, 55 (23.8%) painted tattoo on their body, and 72 (31.2%) were homosexual. Only 3.5% of the participants reported being vaccinated against HBV, and 121 (52.4%) used condoms during intercourse. Conclusions: The serological prevalence of HBV and HCV was low. Nevertheless, vaccination program needs to be strengthened in transgender populations. JCMCTA 2022 ; 33 (2) : 4-7